THE EFFECTIVENESS OF USING VISUAL AIDS INTEGRATED COMMUNICATIVE LANGUAGE TEACHING METHOD IN IMPROVING THE STUDENTS’ SPEAKING ABILITY AT THE SECOND GRADE OF SMAN 1 PINRANG - ,, Rustan; Asik, Nur (ETERNAL (English, Teaching, Learning, and Research Journal), 2016)
This research was aimed to determine the effectiveness of using visual aids integrated communicative language teaching method in improving the students’ speaking ability at the second grade of SMAN 1 Pinrang. Therefore, the principle research problem was only one in this research, that is to what extent is using visual aids integrated communicative language teaching method effective in improving the students speaking ability at the second grade of SMAN 1 Pinrang? The researcher applied experimental method with the non-equivalent controlled group design. The population of this research was the second grade students at SMAN 1 Pinrang, which consist of 150 students. The sample was taken by using purposive sampling. So, the researcher took two classes in this research, one class as experimental class which consisted of 30 students and one class as controlled class. The data were collected through pre-test and post-test. Based on the research findings, from the test, the researcher concluded that the use of visual aids integrated communicative language teaching method effective in improving their achievement in speaking ability, especially for fluency and accuracy. It proved from the mean of the both of classes, which was the mean score of post -test of experimental class was 59,2 while the mean score of control class was 45.6. The result of t-test also shown that the visual aids integrated communicative language teaching method is effective in improving students’ speaking ability because t -test, 4.94, is higer than t-table, 2.000 (4.94>2.000). The research result of this study implies that English teachers should use communicative language teaching method integrated visual aids to develop their techniques and methods in teaching speaking, the students use pictures and videos in improving their speaking ability as it can help them with the new ideas, vocabularies, and pronunciations, the future researcher develops some dimensions which have not been developed in this research like using different students’ population or students’ condition viewed from the students’ habit or interest.